2020
DOI: 10.1080/16878507.2020.1762528
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and awareness of ionizing radiation risks among Saudi Obstetricians

Abstract: This study was conducted to assess Saudi obstetricians' knowledge and awareness of the risks of ionizing radiation. Following a cross-sectional study design, 130 obstetricians in Saudi Arabia were included. A study questionnaire was designed and developed by the researcher. Most participants (69.2%) did not undergo training on radiation risk, while their activities related to radiation risk included attending accredited courses (5.4%); on-the-job training (21.5%); attending workshops, seminars, or conferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…18 Some studies have also reported the lack of knowledge among healthcare professionals. 19,20 But attending health education programs has shown increased awareness levels in them. 21 However, all of them agree that education and awareness must take place.…”
Section: Discussionmentioning
confidence: 99%
“…18 Some studies have also reported the lack of knowledge among healthcare professionals. 19,20 But attending health education programs has shown increased awareness levels in them. 21 However, all of them agree that education and awareness must take place.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed in their research measuring radiological imaging knowledge and practice among local doctors, radiologists, and interns that the impression was poor and might reflect a predisposition to overuse radiation, which could have negative consequences [4]- [7]. It has been discovered in that participants had an average lifetime risk of cancer related with radiological testing and had analyzed the underestimating of risk of treatments using radiation, particularly in primary care [8]- [10].…”
Section: Introductionmentioning
confidence: 99%